Redeeming the priestly role of theology for the land of Africa - W'Ehusha, Lubunga (Old Testament essays, 2014)
The article is an attempt to rise to the challenge raised by Peet van Dyk in his contribution to Old Testament Essays 22/1, where he calls upon South African OT scholars to develop a relevant ecotheology that can address current ecological issues. This challenge becomes more urgent as the environmental crisis gets increasingly serious, and as problems related to land distribution continue to affect social, political and economic life in many African countries. However, there are pertinent issues to be dealt with if theologians want to contribute toward solving current ecological problems. On the one hand, Christianity is accused of having inspired the industrialised, capitalistic society of the Western world to dominate and to abuse nature. On the other hand, several theological critics consider the biblical message as so overwhelmingly anthropocentric that it virtually cancels the possibility of an adequate articulation of environmental concerns. Notwithstanding criticisms regarding the contribution of Christianity and of the Bible in contributing to the environmental crisis, this article advocates redeeming the priestly role of theology in order to address the effects of the global ecological crisis on the African continent. In this article the author suggests that, if theology has been used to encourage humankind to dominate and abuse nature, it can be redeemed by playing a significant priestly role instructing people how to care for and restore nature.